Securing Our Natural Wealth A Policy Agenda for Sustainable Development in India and for Its Neighboring Countries - Bandyopadhyay, Debashis (South Asia Economic and Policy Studies,, 2018)
This book explores various aspects of Intellectual Property Rights (IPR) regimes with regard to plant-variety protection and farmers' rights; traditional knowledge; geographical indications, genetically modified crops; and access to genetic resources within the broad ambit of Trade-Related Aspects of Intellectual Property Rights (TRIPS), the Convention of Biological Diversity and other treaties/protocols. Enumerating the governance provisions for India and some of its neighboring countries, including Nepal, Sri Lanka, Bangladesh, Bhutan, Thailand and Myanmar, the book synthesizes a policy agenda to drive sustainable development. Further, it assesses and interprets the status quo, and discusses key issues and implications. By comparing various governance frameworks in South Asian countries, it attempts to bridge policy issues concerning development, IPR and international studies.